Indocyanine green fluorescence image-guided total laparoscopic living donor right hepatectomy: The first case report from Mainland China - Meng, Xiangfei (Int J Surg Case Rep, 2018)
INTRODUCTION: Total laparoscopic living donor right hepatectomy (TLDRH) is sporadically reported worldwide. Liver transection margin used to be determined by ischemic demarcation or intraoperative ultrasonography. To identify the site of bile duct division relied on preoperative MRCP and intraoperative cholangiography, which is experience demanding. PRESENTATION OF CASE: A 34-year-old man volunteered for living donation to his brother who suffered decompensated HBV-related cirrhosis. Right lobe donation without MHV fulfilled the volumetric criteria. After hilum dissection, ICG was injected into the right portal branch. Right lobe was transected tracing the real-time fluorescence-enhanced borderline and the course of MHV. The right bile duct was transected above the bifurcation that was fluorescently visualized within the parenchyma. The liver graft was retrieved from a pre-made suprapubic incision after simple vascular clamping. The warm ischemia time was 6 min. The recipient procedure was successful with back-table graft venoplasty using cryopreserved iliac artery allografts. The donor recovered uneventfully and was discharged from hospital on POD 7. DISCUSSION: The operative time, blood loss and postoperative course of donor is comparable to those undergoing ordinary laparoscopic right hepatectomy in our institute. ICG fluorescence can real-timely visualize the surgical margin and biliary branches of right lobe, which helps preserve every last bit of functional liver volume for the donor and avoid the complicated traditional intraoperative cholangiography. CONCLUSION: TLDRH proves to be achievable in surgical teams confortable with both laparoscopic hepatectomy and LDLT. ICG fluorescence navigation could make the procedure simplified, safer and more accurate. More practice and technical modification are necessary.